Agency and Moral Status - Sebo, Jeff (Journal of moral philosophy, 2017)
According to our traditional conception of agency, most human beings are agents and most, if not all, nonhuman animals are not. However, recent developments in philosophy and psychology have made it clear that we need more than one conception of agency, since human and nonhuman animals are capable of thinking and acting in more than one kind of way. In this paper, I make a distinction between perceptual and propositional agency, and I argue that many nonhuman animals are perceptual agents and that many human beings are both kinds of agent. I then argue that, insofar as human and nonhuman animals exercise the same kind of agency, they have the same kind of moral status, and I explore some of the moral implications of this idea.